RELIGIOUS MODERATION IN THE IMPRESSION OF THE ACADEMIC COMMUNITY OF STATE ISLAMIC RELIGIOUS COLLEGES LAMPUNG - Zulaikhah, Siti; Gani, A. (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aims to examine and explain the impression of religious moderation in State Islamic Universities (PTKIN) in Lampung. The research subjects were lecturers and students of Universitas Islam Negeri (UIN) Raden Intan Lampung and Institut Agama Islam Negeri (IAIN) Metro Lampung. This research uses a descriptive qualitative-quantitative research design (mix method). The research model used is concurrent embedded or balanced combination models. The information collection techniques used were questionnaires and interviews. Information reduction, information presentation, and information verification techniques were used to assess qualitative data, while statistical information analysis was used to analyse quantitative data. Based on the results of the study, the proportion of respondents who stated